Fractal Analysis on the Crushing Characteristics of Soil-Soft Rock Mixtures under Compaction - Fengyun Hu; Keneng Zhang; Kaofei Zhu; Bintian Li; Zhao Zhang; Yong He (Fractal and Fractional, 2024)
Soil-rock mixtures (SRM) are extensively utilized as filling materials in engineering slopes and roadbeds. A comprehensive understanding of the crushing characteristics of SRM during compaction is essential for precisely controlling its mechanical properties, particularly when dealing with SRM comprising soft rock blocks. This study conducted heavy compaction and screening tests to investigate the crushing and compaction behaviors of soil-soft rock mixture (SSRM) with varying coarse particle content (P5 content), the primary focus was primarily on analyzing the double fractal characteristics of coarse and fine particles. The research findings are as follows: with the increase of P5 content, the maximum dry density of SSRM initially rises and then declines, reaching its peak when P5 content is 70%. Soft rock blocks in SSRM exhibit extreme fragility during compaction, the crushing index of coarse particles exhibits a linear increase with the rise in P5 content, whereas the crushing index of fine particles displays a “double peak” characteristic. After compaction, a linear positive correlation is observed between the fractal dimension and the crushing index of coarse and fine particles. With the increase in P5 content, the slope of the relationship curve between the fractal dimension and the crushing index of coarse particles remains relatively constant, while the intercept gradually decreases. Moreover, the fractal dimension of fine particles effectively reflects the compaction characteristics of SSRM, and the relationship between the fractal dimension of fine particles and dry density aligns with the compaction curve of SSRM.